CNS Involvement of Virus-associated Hemophagocytic Syndrome: MR Imaging Appearance - Forbes, Kirsten P.N.; Collie, Donald A.; Parker, Alistair (American Journal of Neuroradiology, 2000)
Summary: The MR imaging appearance of a case of virus-associated hemophagocytic syndrome complicated by diffuse CNS infiltration is presented. Virus-associated hemophagocytic syndrome is a rare condition, precipitated by viral infection and characterized by proliferation of benign histiocytes with phagocytosis. In severe cases, the CNS may be involved.